COVID-19 will mostly spare young children; the economic crisis will not - Ruel, Marie T.; Headey, Derek D. (International Food Policy Research Institute, 2022)
In a pair of commentaries published in The Lancet in August 2020, we and our colleagues in the Standing Together for Nutrition Consortium (STfN) and the leaders of four UN agencies called for immediate action to address the escalating problems of child malnutrition and excess mortality triggered by the COVID-19 pandemic (Fore et al. 2020; Headey et al. 2020). Although child mortality from the virus itself is low compared to other age groups, the social, economic, and health systems crises it has prompted pose a serious threat to young children’s nutrition, health, and survival in low- and middle-income countries (LMICs).